Understanding, perceptions and reliance of financial statements among Malaysian insurance policy holders / Zuraidah Mohd Sanusi ... [et al.] - Mohd Sanusi, Zuraidah; Othman, Suaini; Mohd Noor, Rohaya; Omar, Normah; Dennis, Taylor (Universiti Teknologi MARA Cawangan Pahang, 2004)
Customers of today’s world are exposed to a variety of products and investments. It is best that they are aware of the consequences on their return of investment. Thus, this study examined the level of understanding and reliance of insurance policy holders on financial statements. Evidence was provided on the denotative meaning accorded to financial terms found in corporate reports, using the instrument developed by Haried (1972, 1973) and further adapted by Chudry et. al. (2000). A survey was conducted on 312 insurance policy holders. The study also focused on the denotative meanings of semantic analysis. For the purpose of this analysis, six financial terms were chosen: turnover, profit from operations, loss from operations, accumulated depreciation, dividend per share and goodwill. From the denotative analysis, the respondents scored high level of understanding on terms such as turnover and dividend per share.